ANALISIS TINGKAT KONSUMSI KAYU BAKAR PADA USAHA PENGOLAHAN TAHU DI KOTA MASOHI KABUPATEN MALUKU TENGAH - Armerdyanto, Andika; Siahaya, Troice; Sahureka, Mersiana (MARSEGU : Jurnal Sains dan Teknologi, 2025)
The aim of this research is to determine the level of firewood consumption and the factors that influence firewood consumption in several tofu processing businesses in Masohi City, Central Maluku district. This research uses a survey method. Data obtained from interviews and observations include wood sources, types of firewood, volume of firewood used in processing tofu. The results of the research show that there are 17 types of firewood with the highest use being black belo wood (Diospyros pilosanthera Blanco). There are 6 villages as a source of firewood for tofu processing businesses in Masohi, namely Baru Village, Hollo, Nua Nea, Tamilouw, Sepa, Gunung Sugiarto. The highest consumption of firewood is pure tofu and tempeh business with a wood volume of 357.21 cubic meters per year. Factors that influence the level of firewood consumption in tofu processing are the amount of soybean porridge that is boiled, the cost of procuring firewood, the frequency of boiling, and the number of types of wood.